The dik-diks of Guli Waabayo: late Pleistocene net-hunting and forager sociality in eastern Africa - Jones, MB (Springer, 2023)
Net-hunting is closely linked to organized labor and hunter-gatherer cooperation in many world regions. At the Rifle Range Site (RRS) in southern Somalia, scholars have argued that Later Stone Age (LSA) foragers developed specialized strategies for hunting dwarf antelope—possibly using communal net-drives—to facilitate developing concepts of territoriality around resource15 rich inselberg environments during a wet period in the early and middle Holocene. Unfortunately, a lack of radiocarbon dates and faunal data limited detailed zooarchaeological perspectives on changing hunting patterns at the site. The large and well-dated dwarf antelope bone assemblage (1,263 specimens) from nearby Guli Waabayo (GW) rock shelter, on the other hand, provides an opportunity to explore proposed relationships between net-hunting and LSA social and economic reorganization in southern Somalia ~26-6 thousand years ago (ka). Consistently high dik-dik frequencies (55.2-71.9%) and mortality profiles comprised of individuals from all age groups throughout the sequence do not support previous arguments at RRS that associate specialized dwarf antelope hunting with territoriality and Holocene climatic amelioration. Instead, they suggest that LSA foraging groups regularly hunted dik-dik with nets over a ~20,000-year period beginning as far back as the arid Marine Isotope Stage 2, 29-14.5 ka. Findings from this study complement recent arguments for greater economic variability in Late Pleistocene eastern Africa and extend discussions of forager social change further back in time than previously considered.